Evaluation of non-stress test as predictor of perinatal outcome in high risk and low risk pregnancy: a prospective study - Amin, Hardik; Dashora, Sanchita; Sharma, Rajrani; Joshi, Ruchi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: NST is simple, cheap, non-harmful, easily repeated, and cost effective with low maintenance profile. NST is a very effective method to investigating the intrauterine growth retardation (IUGR), late pregnancy, premature birth, multiple pregnancy, Rh sensitivity, diabetes, liver disease, decreased bowel movements, oligohydramnios etc. Objectives were to evaluate the efficacy and role of antenatal NST in improving perinatal outcome in high-risk pregnancies. Methods: This prospective study was done among 100 pregnant women (group A: high risk pregnancy, n=50, group B: low risk pregnancy, n=50). Nonstress test was done for 20 minutes if the test was inconclusive or nonreactive. It was continued for another 20 minutes extended CTG. Fetal stimulation was also done. The NST done before onset of labour was used as reference. Interpretation if NST tracings was done according to ACOG guideline. Results: Around 58% participants of high-risk group and 82% of low-risk group had ‘reactive’ and NST tracings respectively. Almost 36% participants of high-risk group and 16% of low-risk group were delivered baby by LSCS method. Around 24% participants of high-risk group and 10% of low-risk group had meconium-stained amniotic fluid. Around 66% babies of participants of high-risk group and 24% of low-risk group were admitted in NICU. The mean birth weight of babies of high-risk group participants was 2.52 kg and of low-risk group participants was 2.85 kg. Conclusions: Present study reveals significant difference between reactive and nonreactive NST in terms of Apgar scores and NICU admissions in both the groups. Hence judicious use of NST will certainly help in timely identification of at-risk fetuses thereby avoiding unnecessary delay in intervention.